Mehr Teilhabe ermöglichen: Wie Schüler:innen besser auf ihre berufliche Ausbildung vorbereitet werden können - Christine Steiner; Frank Tillmann (Wirtschaftsdienst, 2023)
– In view of the cross-sectoral shortage of skilled workers in Germany, the structural deficits and dysfunctionalities in vocational education and training are currently being discussed intensively and, among other things, the further development of vocational orienta-tion is recommended. The COVID-19 pandemic has not only massively limited the possibilities for vocational orientation, but has also made existing deficits more apparent. After a brief look at the status quo of vocational guidance, this article uses current findings to trace the possible consequences for young people and discusses some consequences for the future development of vocational guidance.
Keywords: I21; I23; I29; 330; Berufsbildung; Betriebliche Ausbildung; Deutschland; Berufsbildung; Betriebliche Ausbildung; Deutschland